Solubilidade do carbonato de cálcio em misturas aquosas contendo etilenoglicol, cloreto de sódio e CO2: dados experimentais e modelagem - Vieira, Beatriz Idalina de Oliveira (2019)
In the course of the oil and natural gas production process, light hydrocarbon such as methane can be encapsulated by water, and gas hydrates can be formed. These compounds, formed at high pressures and low temperatures, act in a way to interrupt the flow in the pipes, making the process costly, as they may compromise the safety of the operation. In this sense, thermodynamic inhibitors of hydrate formation, such as monoethyleneglycol (MEG), are used. The MEG is injected into the head of the wells in order to ensure the economic feasability and safety of the process. However, this inhibitor may lead to favoring the precipitation of the salts present in solution in the forming water, and thus, to support the deposition of these salts in the pipes. As a result, the lines can be blocked, culminating in unit stoppage. In this sense, salt solubility data are essential to assist the industry in the operation and optimization in the MEG Regeneration Unit (MRU), where such a plant has the partial objective of removing the salts present in the rich MEG. Thus, this work aims to study the solubility conditions of calcium carbonate (CaCO3) in aqueous mixtures of MEG, sodium chloride (NaCl) and carbon dioxide (CO2). It also aims to develop an empirical model to determine the solubility of CaCO3 as a function of CO2 partial pressure (PCO2), temperature, MEG concentration and NaCl concentration. Knowing these variables, the model can be applied to predict the possibility of precipitation of the carbonate, as well as the amount precipitated. A series of systematic data was correlated, and is able to predict carbonate solubility data under conditions similar to those of the MRU of the Mexilhão platform. Experiments were performed by analytical and synthetic methods by sweeping the entire MEG concentration at 25 °C, 101 kPa and NaCl concentration. A decrease in solubility of the salt was observed with increasing MEG. For systems in the absence of CO2, simulating out of the well conditions, the slow kinetic dissolution of CaCO3 in aqueous solution at 25 °C was observed. In addition, conductivity was studied as a synthetic method for the determination of CaCO3 in locu, and a relationship of direct dependence of this measurement was obtained for the solubility of CaCO3 measurements under the operational conditions of interest.